Growth Volatility in Belize - Longmore, Rohan; Antonio, Matias; Oliveira, Luiz Edgard; McLeod, Roger (World Bank, Washington, DC, 2019)
An open economy structural vector autoregressive (SVAR) model is developed for Belize with the objective of identifying the main factors behind the volatility in output growth. A MarkovSwitching VAR (MS-VAR) model is also employed to explore whether the response to shocks is the similar across different economic states. The paper finds that Belize is one of the most volatile economies in Latin America and the Caribbean. Most this is volatility is driven by fluctuations in the economic growth of its main trading partners – United States and Mexico - and domestic price movements. The impact of these variables differs significantly depending on the prevailing economic conditions in Belize. Notably, the influence of trading partner’s GDP on growth weakens during periods of intense volatility suggesting that the authorities may need to invest more in developing countercyclical measures to minimize the duration of instability. The paper also confirms that higher output volatility undermines the pace of economic expansion in the country and has kept growth in Belize lower than otherwise possible.